Evaluation of colour and texture of a Portuguese traditional sweet: “egg chestnut” - Guiné, Raquel (2016)
This work aimed to evaluate the colour and texture of a Portuguese traditional sweet “egg chestnuts” along a storage period of 12 days under refrigeration. For this, the colour coordinates were measured through a colorimeter and the textural parameters were evaluated by compression and puncture tests using a textutrometer. The results showed that the colour coordinates do not vary along time, corresponding to very low values of total colour difference. Hardness, chewiness and springiness decreased in the first 3 days but after that the values were maintained approximately constant. In contrast, resilience and cohesiveness did not change along time. While crust firmness increased along storage, both the flesh firmness and stickiness did not change. The adhesiveness measured through the penetration test decreased considerably from the first to the last day. Hence, it was concluded that colour is better preserved than texture along a 12 day storage period under refrigeration.